IMPLEMENTATION OF KOSA RUPA BOOK: DRAWING AND COLORING OF ELEMENTARY SCHOOL TEACHERS IN PEGAYAMAN VIILAGE, BALI - Hadi Alhail; Vincensius Jovan Rubijanto; Akram Musthafa; Della Purnama; I Gusti Agung Gede Aditya Utama (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
Difficulty in teaching learning related to drawing from teachers to students is a problem experienced by elementary school teachers in Pegayaman Village, previous research provides information that there is one media to help teachers improve their drawing and coloring competencies, namely